2022
DOI: 10.1021/acs.orglett.2c02512
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Induced Highly Regioselective and Stereoselective Oxysulfonylation of Alkynes for the Synthesis of (E)-β-Phenoxy Vinylsulfones

Abstract: A highly efficient visible light-induced regioselective and stereoselective oxysulfonylation of alkynes with arylsulfonate phenol esters has been developed. This photocatalyst-and metal-free method proceeds smoothly under very mild conditions and exhibits a broad substrate scope, providing (E)-β-phenoxy vinylsulfones in moderate to excellent yields. Mechanistic studies indicated the involvement of an electron donor− acceptor complex-mediated radical process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…42 Zhang et al reported the violet (400 nm) light-induced synthesis of (E)-β-phenoxyvinylsulfones via an EDA complex-mediated radical reaction. 43 Using visible light, we, 44 Mutra et al, 45 and Gurawa et al 46 have recently shown that the photoinduced addition of RSO 2 I to internal alkynes in acetonitrile occurs with high yields and regio-and stereoselectivity. Such a reaction would represent in principle an ideal atom-saving process.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…42 Zhang et al reported the violet (400 nm) light-induced synthesis of (E)-β-phenoxyvinylsulfones via an EDA complex-mediated radical reaction. 43 Using visible light, we, 44 Mutra et al, 45 and Gurawa et al 46 have recently shown that the photoinduced addition of RSO 2 I to internal alkynes in acetonitrile occurs with high yields and regio-and stereoselectivity. Such a reaction would represent in principle an ideal atom-saving process.…”
Section: Introductionmentioning
confidence: 94%
“…42 Zhang et al reported the violet (400 nm) light-induced synthesis of ( E )–β-phenoxyvinylsulfones via an EDA complex-mediated radical reaction. 43…”
Section: Introductionmentioning
confidence: 99%
“…The reaction went smoothly in the absence of any photosensitizer and the reaction went via an electron donor‐acceptor complex‐mediated radical process (Scheme 14). [17a] As per the suggested mechanism, an intermolecular electron donor‐acceptor complex is formed between arylsulfonate phenol ester ( 23 ) and the enolate of DMA in the presence of a base. Next, as a result of visible‐light irradiation the excited EDA complex underwent an intracomplex single‐electron transfer (SET) to generate a radical anion ( A ) and α‐carbamoyl radical.…”
Section: Outlines Of the Reactions Involving C−s Bond Formationmentioning
confidence: 99%
“…5 Owing to the interest in its synthesis, 6 there are numerous synthetic methods for vinyl sulfone synthesis. 7 Usually, the difunctionalization of alkynes 8 can provide an efficient and direct way via the concomitant introduction of two different functional groups 9 (Scheme 1a). For instance, Tang's group 10 reported a direct disulfonylation reaction of terminal alkynes and sodium sulfinates with a Cu( i ) catalyst (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%